Some Biological Features of Empoasca decipiens Paoli on Sesame in Varamin - Ahmad Parvin (نامه انجمن حشره‌شناسی ایران)
According to our study, there are mainly three species of leafhoppers (Cicadellidae) on sesame field in Varamin (1989 - 1990): l- Empoasca decipiens Paoli